EMBODYING ECOLOGICAL - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Embodying Ecological Policy in Defending the Leuser Ecosystem Area for Sustaining Collective Life Triono Eddy Lecturer of Graduate Law School Muhammadiyah University of North Sumatra (UMSU) The destruction stemmed from the wrong policy or paradoxical policy of the government, blunder regulation in the form of conflicted norms, legal vacuum, and blurred norms in regulating the Leuser ecosystem. The management and protection of the Leuser ecosystems and the maintenance of sustainability of collective life .*** 1. Introduction The term Leuser Ecosystem Area (LEA) is regulated in the Ministerial Decree No. 227/1995. The two provinces of Aceh and North Sumatra. massively.4 ISSN 2220-8488 (Print), 2221-0989 (Online) ©Center for Promoting Ideas, USA www.ijhssnet.com Over the years, LEA provides ecological functions such as water supply, protector of landslides, droughts and floods5, and climate controls. aimed at exploring an appropriate strategy and approach in embodying the ecological policy in defending the Leuser ecosystem area for maintaining the sustainability of collective life.